Effect of Government Entrepreneurial Policies on Indigenous Women Entrepreneurs in North-Central, Nigeria - Bamidele, AbdulRasheed Hamza; Hamzat, Ibrahim Bamidele; Adegoroye, Adedibu Abayomi (NIU Journal of Social Sciences; Vol 10 No 4 (2024): NIU Journal of Social Sciences, Vol. 10 No. 4 December 2024DO - 10.58709/niujss.v10i4.2027, 2024)
This study assesses the effects of government entrepreneurial policies on indigenous women entrepreneurs in North-Central Nigeria, focusing on how entrepreneurial activities such as producing Peanut-Cake (Kuli-Kuli) and Handwoven Cloth (Aso Ofi) etc contribute to poverty alleviation among rural women. It assesses how the National Social Investment Program (NSIP) and the Government Enterprise and Empowerment Program (GEEP) affect the economy of rural women empowerment and identifies the difficulties these women encounter. The research work adopts a descriptive survey approach, the research makes use of both primary and secondary data sources: primary data were collected through a questionnaire while secondary data was sourced from official documents of registered Indigenous women entrepreneurs and other sources. Empowerment theory was adopted to analyse the impact of these policies. Findings illustrate that, despite the programs' goals to enhance their financial resources and access to the market, their effectiveness has been limited. Key issues include insufficient access to capital, value-restrictive cultural norms, and inadequate program support. The study recommends that entrepreneurial policies should be designed to meet the needs of Indigenous women entrepreneurs, improve access to financial resources, expand training opportunities, and address cultural barriers in the studied area Keywords: Entrepreneurial, Women, Policies, Indigenous